OPTIMALISASI PEMBELAJARAN MELALUI KEGIATAN BERMAIN PADA ANAK SD - Siska Safitri; Haifaturrahmah; Yuni Mariyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning Which Good in level School Base very crucial for child development. Study in a number of year final has disclose that moment play activities entered in process learning this matter can repair quality as well as effectiveness for student Elementary school. Article This serve review literature study checking diki How method increase learning for children Elementary School with equalize activity Study And play. Review This discuss various study previously Which emphasize profit from play in Study For child child in SD. This including implementation method teaching Which innovative, utilization game educational, and creation environment Study Which support creativity as well as interaction between students. Review This library also discusses challenge Which Possible arise when try combine Study And play, like election material Which in accordance and assessment learning outcomes.